PENGARUH KEPEMIMPINAN TRANSFORMASIONAL PADA KINERJA DENGAN KESAMAAN VISI ANTARKARYAWAN SEBAGAI VARIABEL PEMEDIASI - Wisnu Prajogo (Jurnal Riset Manajemen dan Bisnis, 2013)
This research examines the direct and indirect influence of transformational leadership to performance, with employee’s shared vision as the mediating variable. 504 respondents taken from a purposive sampling based on their occupational characteristics participated in this research. The results reveal that transformational leadership has no influence to employee performance, meanwhile transformasional leadership has positive influence to shared vision among employees, and shared vision among employees has positive influence to employee performance. This research also found that shared vision among employees has a full mediation role in the relationship of transformasional leadership and employee performance. Keywords: transformational leadership, shared vision among employees, employee performance